PENERAPAN METODE FINITE STATE MACHINE PADA GAME EDUKASI SEJARAH “LEGACY OF SISINGAMANGARAJA XII” MENGGUNAKAN RPG MAKER MV - Prayogo, M. Fahrozy; Usman, Ari; Khairani, Sumi (SKANIKA: Sistem Komputer dan Teknik Informatika, 2025)
Legacy of Sisingamangaraja XII" is an educational game designed to enhance young people's understanding of the struggle of Sisingamangaraja XII, an Indonesian national hero who fought against Dutch colonialism in the 19th century. This research employed the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) to ensure the game's effectiveness. Developed using RPG Maker MV and the Finite State Machine (FSM) method, the game successfully increased interactivity by regulating the dynamic behavior of Non-Playable Characters (NPCs), enabling dialogues, providing clues, and responding to player actions realistically. The results of the evaluation showed that 81% of respondents felt positive about their gaming experience, 82% experienced an increase in historical understanding, and 84% considered the game to be an effective learning medium. FSM proved to enhance the depth of interaction and realism in gameplay, providing an immersive and enjoyable learning experience. This research concludes that "Legacy of Sisingamangaraja XII" is an effective and innovative interactive learning tool with potential for application to other historical materials.